Produksi Protease Alkalis Termostabil Dari Aspergillus flavus DUCC- K225 Dengan Ammonium Sulfat Sebagai Sumber Nitrogen - Putra, Mohammad Affan Dwica; Rukmi, MG Isworo; Pujiyanto, Sri; Mulyani, Nies S (Bioma : Berkala Ilmiah Biologi, 2019)
Protease  is a protein hydrolytic enzyme which  can be generated by a variety of microorganisms, including  mold. Aspergillus flavus K225, DUCC is indigenous mold isolated from lime soil of Madura which is  have potential as a alkaline protease  producer. This research aims was to know the effect  of ammonium sulfate as nitrogen source for the production of protease enzymes by Aspergillus flavus DUCC-K225. The production of alkaline  protease were conducted in  submerged culture medium with agitation. Fermentation medium used was modification Czapeks Dox Broth containing 2% casein. Incubation is carried out for 7 days.  The results showed that ammonium sulfate is a good source of nitrogen for growth and production of aklaine protease enzyme, which is demonstrated by  higher dry weight, the protease activity, the protein content and the specific activities, comparing those  on standard medium using sodium nitrate as N source.